Examples of ecological data synthesis driven by rich metadata, and practical guidelines to use the Ecological Metadata Language specification to this end. (15th September 2011) - San Gil, Inigo; Vanderbilt, Kristin; Harrington, Steve A.
We present two examples of scientific results using a semi-automated data synthesis driven by quality, rich-content metadata: 1) Antarctic climate and 2) effects of drought on biodiversity. We use a framework for semi-automated processing of data supported by quality controlled, content-rich metadata expressed in the Ecological Metadata Language (EML). We discuss a set of common practices for EML newcomers as a valuable guide for the EML use. We provide some simple tools that can be used to address quality control as the EML is generated. Based on our extended EML experience, we make recommendations about the future of EML.